SUBJECT AUTHENTICATION SYSTEM IN WINDOW TRANSACTION OF FINANCIAL INSTITUTION AND TRANSACTION METHOD THEREOF - YAMAZAKI KURUMI (2016)
PROBLEM TO BE SOLVED: To provide a subject authentication system in window transaction of a financial institution for eliminating individualistic determination of subject authentication by a window employee, and performing the subject authentication independently from a count system of the financial institution, and a transaction system thereof.SOLUTION: A subject authentication system in window transaction between a financial institution and a client is configured so that a subject authentication engine 3 which can transmit information to both of a client terminal 1 operated by a client, and a window terminal 2 operated by a financial institution, is installed independently from a count system 4 of the financial institution, and subject confirmation in window transaction is performed by checking and determining engagement of an authentication item 18 which is registered in the subject authentication engine 3 as authentication means 11 in advance by selection of the client, and the authentication item 18 submitted by the client, on the subject authentication engine. A transaction method thereof is also provided.SELECTED DRAWING: Figure 1 【課題】窓口職員による本人認証の属人的判断を排除し、本人認証を金融機関の勘定系システムから独立させて行う金融機関の窓口取引における本人認証システム及びその取引方法を提供することを目的としている。【解決手段】金融機関と顧客との窓口取引における本人認証システムであって、顧客の操作する顧客端末１及び金融機関の操作する窓口端末２の双方と情報伝達可能な本人認証エンジン３を金融機関の勘定系システム４から独立させて設置し、予め顧客の選択によって本人認証エンジン３に認証手段１１として登録した認証アイテム１８と、顧客が提示した認証アイテム１８との契合を本人認証エンジン３において照合・判断することによって、窓口取引における本人確認を行う金融機関の窓口取引における本人認証システム及びその取引方法を提供する。【選択図】図１